METAPHYSICS IN THE PHENOMENA OF THE RAIN TRAINER IN SOCAH VILLAGE - Encung; Zilvani (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to analyze the phenomenon of rain handlers in Socah village. This research uses a qualitative approach. Data collection is carried out by interview, observation and documentation methods. Data analysis uses data reduction, data presentation and conclusions. The results showed that in the transfer of rain itself has a way to move rain including using sandals of orphans that are stolen. This is proven in the transfer of rain there is a metaphysical activity, namely by using the theory of teleksinesis, where the theory has the ability to move inanimate objects using physical members, namely the mind so that it can move clouds that were previously cloudy into bright light. The phenomenon of rain charmers in natural philosophy that occurs in Socah village is to seek the truth of a natural phenomenon that occurs in a situation that guides the way of thinking in the right realm with wisdom in controlling the rain, through certain ways, such as using symbols or tools such as, bottles stuck in holes, sandals tied and thrown on the roof of the house and frogs that are caged and abstained from being hurt and materials that are not hurt. Become another supporter